The Concept of Bioavailability in Natural Pharmaceuticals for Better Therapeutic Outcomes: An Overview - Thorat , Suvarna Sopanrao; Tare, Manoj Sudhakar; Karale, Chandrakant Kashinath (Advanced Concepts in Pharmaceutical Research Vol. 1, 2023)
The idea of bio-enhancer originated from Ayurveda. Numerous methods exist to improve the bioavailability of drugs, with one of the latest being bioavailability enhancers. Herbal bio-enhancers improve bioavailability due to their absorption, safety, and minimal side effects. They increase drug bioavailability, which affects therapeutic efficacy, and when paired with appropriate drugs, enhance their effectiveness. This combination reduces drug dosage, cost, toxicity, side effects, and speeds up the drug's action. The survey aims to explore the concept of bioavailability in natural pharmaceuticals to achieve better therapeutic outcomes, as well as to classify bio-enhancers, understand their mechanism of action, evaluate commercial formulations, and assess future prospects.